Acute physiological derangement is associated with early radiographic cerebral infarction after subarachnoid haemorrhage. Issue 12 (4th July 2006) - Naidech, A M; Drescher, J; Tamul, P; Shaibani, A; Batjer, H H; Alberts, M J
Abstract : Background: Cerebral infarction after aneurysmal subarachnoid haemorrhage (SAH) is presumed to be due to cerebral vasospasm, defined as arterial lumen narrowing from days 3 to 14. Methods: We reviewed the computed tomography scans of 103 patients with aneurysmal SAH for radiographic cerebral infarction and controlled for other predictors of outcome. A blinded neuroradiologist reviewed the angiograms. Cerebral infarction from vasospasm was judged to be unlikely if it was visible on computed tomography within 2 calendar days of SAH or if angiography showed no vasospasm in a referable vessel, or both. Results: Cerebral infarction occurred in 29 (28%) of 103 patients with SAH. 18 patients had cerebral infarction that was unlikely to be due to vasospasm because it was visible on computed tomography by day 2 (6 (33%)) or because angiography showed no vasospasm in a referable artery (7 (39%)), or both (5 (28%)). In a multivariate model, cerebral infarction was significantly related to World Federation of Neurologic Surgeons grade (odds ratio (OR) 1.5/grade, 95% confidence interval (CI) 1.1 to 2.01, p = 0.006) and SAH-Physiologic Derangement Score (PDS) >2 (OR 3.7, 95% CI 1.4 to 9.8, p = 0.01) on admission. Global cerebral oedema (OR 4.3, 95% CI 1.5 to 12.5, p = 0.007) predicted cerebral infarction. Patients with cerebral infarction detectable by day 2 had a higher SAH-PDS than patients with later cerebral infarction (p = 0.025). Conclusions: : Many cerebral infarctions after SAH are unlikely to be caused by vasospasm because they occur too soon after SAH or because angiography shows no vasospasm in a referable artery, or both. Physiological derangement and cerebral oedema may be worthwhile targets for intervention to decrease the occurrence and clinical impact of cerebral infarction after SAH.